Penerapan Senam Sendi Lutut Sederhana dalam Menurunkan Nyeri dan Meningkatkan Mobilitas Fisik pada Pasien Osteoarthritis dengan Gangguan Mobilitas Fisik - Ahmadi Ahmadi; Nonok Karlina; Muadi Muadi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Osteoarthritis is a degenerative joint disease that frequently causes pain, stiffness, and limited physical mobility. This study aimed to describe the implementation of simple knee exercises for an osteoarthritis patient experiencing impaired physical mobility. A descriptive case study method was employed, involving a 61-year-old female patient. The intervention was conducted over three consecutive days. The results showed a reduction in pain scale from 6 to 3, as well as improvements in range of motion (ROM) and mobility. Conclusion: Simple knee exercises are effective as a non-pharmacological intervention for reducing pain and improving physical mobility in patients with osteoarthritis. Nevertheless, the results of this study should be interpreted with caution, as it involved only a single patient and lacked a comparison group. Research involving larger sample sizes and standardized anxiety measurement instruments is needed to strengthen the evidence regarding the effectiveness of SEFT among hemodialysis patients across various renal care settings.